The Need for Adolescent Mental Health Intervention in Primary Health Care - Susan Fitriyana; Hilmi Sulaiman Rathomi; Sara Shafira (Universitas Islam Bandung, 2020)
Mental health problems in adolescents became a global concern. About 10–20% of children and adolescents worldwide experience mental health problems, but only about 10% get medical attention. This study aims to perform an initial screening of adolescent mental health in Bandung, especially adolescents at school age, to get the magnitude of the problem of mental health in adolescents. This research was a cross-sectional study conducted in Bandung. Data collected in December 2018. The study used consecutive sampling to recruit 140 students from junior and senior high schools. The instrument used was the strength and difficulties questionnaire (SDQ) YR1 version, which was filled independently by respondents. Data were analyzed using STATA 13. The results of this study were that the prevalence of mental health problems in adolescents was 21%. The highest aspect was emotional (28%) and conducted problems (21%). There was a significant different male versus female in emotional and conduction problems. In conclusion, the magnitude of the adolescent's mental health problems in Bandung was enormous; thus, interventions at the primary care level and partnership with another sector needed. PERLU INTERVENSI KESEHATAN MENTAL REMAJA DI PELAYANAN KESEHATAN PRIMERMasalah kesehatan mental pada remaja telah menjadi perhatian dunia. Sekitar 10–20% anak dan remaja di seluruh dunia mengalami masalah kesehatan mental, tetapi hanya 10% yang mendapatkan pelayanan kesehatan. Tujuan penelitian ini melakukan penapisan awal besaran masalah kesehatan mental pada remaja usia sekolah di Kabupaten Bandung. Penelitian ini merupakan penelitian potong lintang yang dilakukan di Kabupaten Bandung. Data dikumpulkan pada bulan Desember 2018 menggunakan consecutive sampling dengan melibatkan 140 siswa SMP dan SMA. Instrumen yang digunakan adalah strength and difficulties questionaire (SDQ) YR1 version yang diisi oleh responden. Data dianalisis menggunakan STATA 13. Hasil penelitian didapatkan prevalensi masalah kesehatan mental pada remaja adalah 21%. Aspek penilaian tertinggi berada pada masalah emosional (28%) dan conducting problem (21%). Terdapat perbedaan nilai yang siginifikan untuk aspek emosinal dan conduct problem antara kelompok laki-laki dan perempuan. Simpulan, masalah kesehatan mental remaja di Kabupaten Bandung sangat besar sehingga dibutuhkan penanganan kesehatan mental remaja di tingkat pelayanan kesehatan primer dan kerja sama dengan sektor lain.